Clinical and prehospital survival indicators in blunt trauma: a multivariate analysis - Malvestio, Marisa Aparecida Amaro; Sousa, Regina Marcia Cardoso de (Revista da Escola de Enfermagem da USP, 2010)
The aim of the study was to identify the clinical and prehospital indicators associated to the survival of blunt trauma victims. The Kaplan Meier survival analysis and the Cox proportional hazards model were used to analyze the association of 33 variables to early and late death, proposing multivariate models. The final models until 48 hours post-trauma showed high rates of risk promoted by abdominal injuries, Injury Severity Score >; 25, advanced respiratory procedures and prehospital chest compressions. In the model up to 7 days, a systolic blood pressure in accident site lower than 75mmHg was associated with increased risk of death, and if absent it was associated with higher risk of death after 7 days. The prehospital volume replacement showed a protective effect in all periods. Results suggest that the magnitude of hypoxemia and hemodynamic instability due to bleeding had a significant influence on early and late death in this group of victims.